1996
DOI: 10.3758/bf03207550
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving self-motion in depth: The role of stereoscopic motion and changing-size cues

Abstract: During self-motions, different patterns of optic flow are presented to the left and right eyes. Previous research has, however, focused mainly on the self-motion information contained in a single pattern of optic flow. The present experiments investigated the role that binocular disparity plays in the visual perception of self-motion, showing that the addition of stereoscopic cues to optic flow significantly improves forward linear vection in central vision. Improvements were also achieved by adding changingsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
96
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 39 publications
12
96
5
Order By: Relevance
“…Another intriguing finding is the enhancement of selfmotion perception with the addition of stereoscopic motion cues (Palmisano, 1996). The finding that perceived 3-D shape influences perceived heading (Beusmans, 1998) also suggests that depth information may contribute to heading perception.…”
mentioning
confidence: 93%
“…Another intriguing finding is the enhancement of selfmotion perception with the addition of stereoscopic motion cues (Palmisano, 1996). The finding that perceived 3-D shape influences perceived heading (Beusmans, 1998) also suggests that depth information may contribute to heading perception.…”
mentioning
confidence: 93%
“…Palmisano (1996) reported that stereoscopic presentation of moving-dot stimuli reduces the latency of vection onset and also increases the percentage of time for which observers report the sensation, relative to monoscopic presentation of the same stimuli. Palmisano's stimuli consisted of fields of randomly positioned dots which expanded outwards, simulating movement at a constant rate towards the observer, while the viewing position and projection plane remained fixed.…”
Section: Postural Responses To Apparent Observer Motionmentioning
confidence: 99%
“…This kind of induced self-motion perception is called "vection". Induced selftranslation perception has been investigated by using linear motion of dots on a flat screen (Johansson, 1977;Kano, 1991;Nakamura and Shimojo, 1999;Ito and Shibao, 1999;Ito, 2004) or by using expanding flow patterns that induce forward vection (Andersen and Braunstein, 1985;Palmisano, 1996). The present study investigates a factor that suppresses vection.…”
Section: Introductionmentioning
confidence: 99%